2017
DOI: 10.1007/s41027-018-0100-0
|View full text |Cite
|
Sign up to set email alerts
|

Migrant workers in urban labour markets in India: wage differentials, assimilation and occupational attainment

Abstract: The paper examines the wage differentials and returns to human capital of migrant and non-migrant workers in the urban labour markets in India. Using unit-level data from the Employment, Unemployment and Migration Survey (2007)(2008), the regression analysis examines the effect of various factors particularly human capital and years since migration in determining wage differentials in different specifications. The results showed that the migrants (both rural and urban) earned higher daily wages than non-migran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Economic migrants are largely working-age men who move from rural to urban areas and within urban areas. These migrants are relatively well off, better educated and belong to higherpaying occupations than non-migrant workers at the destination (Hnatkovska and Lahiri 2015;Khan 2016Khan , 2017Kundu and Saraswati 2012;Vakulabharanam and Thakurata 2014).…”
Section: Internal Labour Migration In Indiamentioning
confidence: 99%
See 2 more Smart Citations
“…Economic migrants are largely working-age men who move from rural to urban areas and within urban areas. These migrants are relatively well off, better educated and belong to higherpaying occupations than non-migrant workers at the destination (Hnatkovska and Lahiri 2015;Khan 2016Khan , 2017Kundu and Saraswati 2012;Vakulabharanam and Thakurata 2014).…”
Section: Internal Labour Migration In Indiamentioning
confidence: 99%
“…Khan (2016) examined the wage differentials between migrants and non-migrants using the quintile decomposition method and found that most of the migrant wage advantage is because of the difference in observable characteristics. The migrant wage advantage is seen not only in the case of formal employment but also among informal workers across industries in the urban labour markets in India (Khan 2017;Srivastava 2011). The descriptive statistics suggest that migrants are more likely to be highly educated, have migrated to places with higher average per capita incomes and highskill regions, and are less likely belong to socially disadvantageous groups.…”
Section: Data and Descriptive Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among others are Meng and Gregory (2005), Breunig et al (2013), Abramitzky et al (2014) and Pakrashi and Frijters (2017). Some of this assimilation literature is on cases of internal migration (Ge, 2017;Khan, 2017). However, few studies have observed the mental health consequences of migration (de Maio & Kemp, 2010;Lerner et al, 2005;Lu, 2010aLu, , 2010b.…”
Section: Past Relevant Researchmentioning
confidence: 99%
“…In the context of internal migration, people tend to move from low‐wage home labour markets, typically in rural areas, to high‐wage destination labour markets, typically in urban areas (Chauvin et al, 2017; Gollin et al, 2014). The convergence of earnings between rural–urban migrants compared to those of the urban population (non‐migrants), or the rural–urban migrants' economic assimilation process, is of great interest in the discourse of social and economic mobility of migrants in developing nations (Effendi et al, 2010; Khan, 2017; Qu & Zhao, 2017).…”
Section: Introductionmentioning
confidence: 99%